Implications of new understandings of gliomas in children and adults with NF1: report of a consensus conference. Issue 6 (14th February 2020) - Packer, Roger J; Iavarone, Antonio; Jones, David T W; Blakeley, Jaishri O; Bouffet, Eric; Fisher, Michael J; Hwang, Eugene; Hawkins, Cynthia; Kilburn, Lindsay; MacDonald, Tobey; Pfister, Stefan M; Rood, Brian; et al.
Abstract: Gliomas are the most common primary central nervous system tumors occurring in children and adults with neurofibromatosis type 1 (NF1). Over the past decade, discoveries of the molecular basis of low-grade gliomas (LGGs) have led to new approaches for diagnosis and treatments. However, these new understandings have not been fully applied to the management of NF1-associated gliomas. A consensus panel consisting of experts in NF1 and gliomas was convened to review the current molecular knowledge of NF1-associated low-grade "transformed" and high-grade gliomas; insights gained from mouse models of NF1-LGGs; challenges in diagnosing and treating older patients with NF1-associated gliomas; and advances in molecularly targeted treatment and potential immunologic treatment of these tumors. Next steps are recommended to advance the management and outcomes for NF1-associated gliomas.